Neurorehabilitation Robot-Assisted for Stroke Recovery: Hybrid Exoskeleton Assistive Limb (HEAL) - Xue, Law Cheng; Mohd Noor, Anas; Zakaria, Zulkarnay; Mohd Nasir, Nashrul Fazli; Nasrul Norali, Ahmad; Nukman Khiruddin, Khalis Danial (IAES Indonesian Section, 2023)
Conventional rehabilitation techniques that require manual intervention and the use of devices are identified as having several drawbacks. These include limited features, fatigue for both patients and therapists during prolonged rehabilitation sessions, time-consuming procedures, high operational and maintenance costs for devices, a lack of motivation for patients, limited accessibility, and challenges in measuring or monitoring rehabilitation progress. In response to these challenges, the Hybrid Exoskeleton Assistive Limb (HEAL) is introduced as a tailored solution with distinctive features. These features include real-time electromyographic (EMG) monitoring, a therapist-friendly graphical interface, and advanced techniques in the rehabilitation process. HEAL utilizes robotics-assisted rehabilitation for repetitive, precise, and controlled movements, enhancing brain-muscle motor function, developing muscle strength, and providing a wide range of motion. The system focuses on upper limb robotic rehabilitation and consists of an EMG to read muscle responses, an Arduino microcontroller for signal processing, and a high-torque precision servo motor for controlling limb movements. HEAL emphasizes the Brain-Muscle-Computer control process rather than passive rehabilitation, which relies on external forces to move the muscles, as demonstrated by the therapist. HEAL is particularly suitable for neurorehabilitation, emphasizing recovery and improvement of function in individuals with neurological disorders or injuries, especially in stroke patients. HEAL's ability to tailor rehabilitation programs individually offers personalized rehabilitation, considering each patient's unique needs, goals, and abilities. It utilizes advanced technologies for targeted and efficient rehabilitation. The HEAL device is cost-saving with a compact design, positioning it as a promising and comprehensive solution in stroke neurorehabilitation.